2013
DOI: 10.1038/mi.2012.49
|View full text |Cite
|
Sign up to set email alerts
|

IL-22 from conventional NK cells is epithelial regenerative and inflammation protective during influenza infection

Abstract: Influenza infection primarily targets the upper respiratory system, leading to a severe destruction of the epithelial cell layer. The role of immune cells in the regeneration of tracheal and bronchial epithelial cells is not well defined. Here, we investigated the production of pro-constructive cytokine, Interleukin-22 (IL-22), in the bronchoalveolar lavage (BAL), trachea, lung tissue, and spleen during influenza infection. We found that conventional NK cells (NCR1+NK1.1+CD127−RORγt−) were the predominant IL-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
174
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(183 citation statements)
references
References 59 publications
7
174
2
Order By: Relevance
“…Collectively, the lack of robust IL-17A and IL-22 production in the lungs of Cl 2 -exposed mice after microbial challenge suggests that a component of Cl 2 -induced immunosuppression is lower induction of soluble antimicrobial factors via the IL-17A and IL-22 axis. Since IL-17A and IL-22 are essential effector cytokines that coordinate the immune response to multiple lung pathogens, including A. fumigatus (26,61), influenza (33,46), Pseudomonas aeruginosa (15), Klebsiella pneumonia (4), and Staphylococcus aureus (17,32), our finding has broad implications for lung host defense mechanisms impaired by Cl 2 gas exposure (and potentially other agents that target the respiratory tract).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, the lack of robust IL-17A and IL-22 production in the lungs of Cl 2 -exposed mice after microbial challenge suggests that a component of Cl 2 -induced immunosuppression is lower induction of soluble antimicrobial factors via the IL-17A and IL-22 axis. Since IL-17A and IL-22 are essential effector cytokines that coordinate the immune response to multiple lung pathogens, including A. fumigatus (26,61), influenza (33,46), Pseudomonas aeruginosa (15), Klebsiella pneumonia (4), and Staphylococcus aureus (17,32), our finding has broad implications for lung host defense mechanisms impaired by Cl 2 gas exposure (and potentially other agents that target the respiratory tract).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory cytokines IL-17A and IL-22 are essential for host defense against multiple viral and bacterial lung pathogens (4,5,21,33). A major function of IL-17A and IL-22 in the lung is the induction of epithelial antimicrobial responses (4).…”
Section: Methodsmentioning
confidence: 99%
“…IL-22 has also been shown in a model of ventilator-induced lung injury to have potential therapeutic benefit (37). It has been shown that the lack of IL-22 is associated with reduced epithelial repair (38) and increased fibrosis (36) in experimental influenza infection. IL-22 can activate STAT3 in airway epithelium and thus can augment the expression of antimicrobial genes as well as aid in epithelial repair (39).…”
Section: Il-22 and Mucosal Immunitymentioning
confidence: 99%
“…However, there are also examples in which NK cells exacerbate morbidity and pathology during lethal dose influenza virus infection in mice (24,25), which indicate that NK cells may play dual roles during influenza virus infection in mice, conferring beneficial or deleterious function depending on the viral dose. Furthermore, production of IL-22 by NK and NKT cells has an important role in the repair of epithelial damage caused by IAV (26,27). Meanwhile, NK cells play important roles in bridging the innate and adaptive immune responses to IAV (28).…”
mentioning
confidence: 99%